Groundwater Supplies for Waterloo Region — The Role of Geology - Farvolden, R. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1982)
Summary The municipal water supply for theKitchener-Waterloo-Cambhdge region ofOntario is provided by wells in Quater-nary gravels. There is justified concernthat future needs cannot be provided forunless a new source is found. Thefavoured solution is a pipeline to LakeErie at a very high cost ($150 million inthe early 70s). Many informed geologistsand engineers believe that additionalgroundwater supplies are available, andperhaps sufficient to meet the forecastdemands. The key factor in a technicalsolution to the problem is better data onthe Quaternary stratigraphy. Funds havenot been made available for basicstratigraphie studies using moderntechniques and as a consequence hydro-geology cannot be used effectively indealing with the problem. The inadequacy of geologic data is notlimited to this region. Basic geologicmapping is lacking generally for assess-ment development and protection of ourgroundwater resources, and somehow wehave to convince government officialsand funding agencies that it will pay tocorrect this deficiency.